Perfil e trabalho docente frente ao projeto maratona do conhecimento no município de Pato Branco - Silverio, Layla Consuelo Constantinopolos (2022)
The Knowledge Marathon Project had been working since 2014 until 2019 and presents as main mission to subsidize actions to improve the quality of education, as well as raise the rates of the municipality in large-scale evaluations. The general aim of this research is to analyze which profile and characterization of the teaching work are expected in the context of the Knowledge Marathon Project. The methodology is consolidated by bibliographic research on the subject. This is the result of problematizing questions that direct the conceptual aspects of this study: What are the political and theoretical conceptions bases the Knowledge Marathon? What knowledge has been prioritized in the theoretical and practical profile of teachers in view of the requirements of improvement in the quality of education? Does the teacher profile established for the Knowledge Marathon and promoted by continuing education make it possible or hinder the autonomous and professional identity? Constituting a descriptive analysis based on these questions, the research is organized into three chapters that converge in order to respond to the general aim. The first brings the conjuncture and dynamics of the Knowledge Marathon in the Pato Branco city and its correlations with the large-scale evaluation policies of which are highlighted characteristics that include curriculum standardization, emphasis on the skills development and immediate results, efficiency, monitoring, accountability and meritocracy present in neoliberal policies. Then, the second chapter points what is the necessary knowledge to teaching in the face of the Knowledge Marathon Project taking into categories of analysis highlighted in the design of the project. Also, it presents a historical survey of the teachers continuing training offered in the city between 2013 and 2019 seeking to identify what extent the contents, concepts and themes offered approach or distance themselves from the dynamics exposed in the Knowledge Marathon, which contains a structure focused on the good performance of students in external evaluations. Finally, the last chapter discusses the constitution of identity and teaching work as procedural and social constituted in relationships, experiences and daily practices that involve theoretical premises, individual context, relationships with other teachers situated in a broader social and political wide scenery. As a conclusion, we pointed the needs of an education Project which contributes to a consolidation of a new vision citizen and school, that could be emancipated or developed beyond financial market requirements.